Quantitative MRI of the hippocampus reveals microstructural trajectories of aging and Alzheimer’s disease pathology - Alfie Wearn; Christine L. Tardif; Ilana R. Leppert; Giulia Baracchini; Colleen Hughes; Jennifer Tremblay-Mercier; John Breitner; Boris C. Bernhardt; Gary R. Turner; R. Nathan Spreng; Sylvia Villeneuve; Judes Poirier; et al. (Proceedings of the National Academy of Sciences, 2025)
Hippocampal degeneration is a feature of both normal aging and Alzheimer’s disease (AD). Prior to macroscopic degeneration, microstructural changes occur such as demyelination, iron deposition, or subtle atrophy, which can be characterized in vivo using MRI. We topographically mapped measures of microstructure and macrostructure across the unfolded surface of the hippocampus in 224 healthy older adults at risk for AD (aged 57 to 87) and 37 younger adults (aged 18 to 37). We describe three spatial regions of unique structural covariance between four parameters sensitive to microstructural tissue properties (R1, MTsat, R2*, PD) and macrostructure (surface thickness), with high convergence with previous spatial segmentations. We demonstrate both cross-sectional and longitudinal associations of microstructure with healthy aging across the lifespan, AD pathological hallmarks, genetic risk, and cognition. These associations had subtle variations across different spatial areas of the hippocampus. We report associations between age and qMRI measures sensitive to macromolecular concentration (R1, MTsat) and paramagnetic susceptibility (R2*), consistent with mechanisms of demyelination and increased iron deposition as key hallmarks of the aging hippocampus and in presymptomatic stages of AD. qMRI measures did not explain more variance in delayed recall than global PET measures, suggesting variation in cognitive performance in aging and incipient AD is influenced by factors beyond hippocampal microstructure. We demonstrate the utility of quantitative MRI to provide greater insight into hippocampal health compared to typical macrostructural measures through “in vivo histology,” opening a window to understanding neuropathological mechanisms in the earliest stages of age- and disease-related neurodegeneration.